Safety, Tolerability, and Pharmacokinetics of Filapixant, a Highly Selective P2X3 Receptor Antagonist, in an Ascending-Single-Dose First-in-Human Study - Klaus Francke; Sybille Baumann; Isabella Gashaw; Stefan Klein; Beate Rohde; Oliver Zolk; Oliver M. Fischer; Christian Friedrich (Pharmaceuticals)
Background/Objectives: P2X3 receptor antagonists have been suggested as a potential treatment for urogenital, respiratory and pain conditions. This first-in-human (FiH) study evaluated filapixant, a new P2X3 receptor antagonist with high receptor selectivity. It was anticipated that filapixant would cause fewer taste-related side effects compared to the unselective P2X3/P2X2/3 antagonist gefapixant and the less selective P2X3 antagonist eliapixant. This study assessed the tolerability, safety and PK of filapixant, the effect of food on PK and relative BA of a tablet vs. solution. Methods: This study (NCT03212586) followed a randomized, double-blind single-ascending-dose design. A total of 72 healthy male subjects received a solution (6–60 mg) or immediate-release tablets (120–1250 mg) of filapixant or corresponding placebo in fasted state. The subjects at 60 mg were re-dosed with 60 mg tablets in both fasted and fed states. The endpoints included PK parameters, dose proportionality, adverse events, and taste assessments (taste strips; dysgeusia questionnaire). Results: Filapixant showed dose-proportional PK with a half-life (about 10–15 h), supporting once-daily dosing. Food minimally affected PK and BA was comparable between tablet and solution. Filapixant was well tolerated; however, the number of taste side effects was unexpectedly high. Comparing the results observed across clinical filapixant studies, the threshold for such side effects seems to be well below the in vitro IC50 for P2X2/3. Conclusions: Treatment with filapixant was safe and well tolerated. Filapixant showed dose-proportional PK, bioavailability similar to that of a solution and a tablet, and a minor effect of food on PK. The number of taste side effects was unexpectedly high considering the high in vitro P2X3 receptor selectivity. Factors other than selectivity are needed to explain taste profile differences between P2X3 antagonists.